ADSORPTION OF COOMASSIE BRILLIANT BLUE R-250 DYE ONTO NOVEL ACTIVATED CARBON PREPARED FROM NIGELLA SATIVA L. WASTE: EQUILIBRIUM, KINETICS AND THERMODYNAMICS RUNNING TITLE: ADSORPTION OF BRILLIANT BLUE DYE ONTO NIGELLA SATIVA L. WASTE ACTIVATED CARBON - Nour T. Abdel-Ghani; Ghadir A. El-Chaghaby; El-Shaimaa A. Rawash; Eder C. Lima (Journal of the Chilean Chemical Society, 2017)
In this paper a novel adsorbent was prepared from Nigella sativa L. waste and used for the removal of Coomassie Brilliant Blue dye from wastewater. The preparation of Nigella sativa waste carbon (NSWC) was achieved by adding concentrated sulfuric acid to the precursor material at an impregnation ratio (1: 1) and the mixture was left overnight. The resulting material was washed with sodium bicarbonates and finally oven dried. The kinetics of coomassie brilliant blue adsorption onto NSWC was investigated by three kinetic models. The pseudo-second order model (R2 = 0.99) was the best model fitted the experimental data.The equilibrium results revealed that Freundlich model was the best isotherm model fitted (R2= 0.994). Also the value of the Freundlich exponent (n) was found to be 1.174 suggesting the favorable dye adsorption onto NSWC. The thermodynamics results indicated negative values of ΔG proving the spontaneous nature of Brilliant Blue dye adsorption on NSWC. The exothermic nature of the adsorption was also confirmed by the negative value of change in enthalpy ΔH°. Also, the negative value of the activation entropy ΔS° demonstrates the decreased randomness at the solid–solution interface during adsorption. The present study results suggest the possible use of a waste such as Nigella sativa L. waste as a precursor for the development of a new cheap and efficient adsorbent that could be used in dyes removal from wastewater.